2010
DOI: 10.1016/j.jcrs.2009.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 intrastromal corneal ring segment models in the management of keratoconus

Abstract: Although both ICRS models were effective and safe in managing keratoconus, the Keraring ICRS led to more improvement in CDVA and UDVA and a greater reduction in the maximum K value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 25 publications
(30 reference statements)
3
66
0
2
Order By: Relevance
“…There are several reports that show the efficacy and safety of ICRS to improve cornea shape and visual quality of keratoconic patients [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Depending on their arc, thickness and zone of implantation, surgeons can find different types of ICRS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several reports that show the efficacy and safety of ICRS to improve cornea shape and visual quality of keratoconic patients [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Depending on their arc, thickness and zone of implantation, surgeons can find different types of ICRS.…”
Section: Discussionmentioning
confidence: 99%
“…KeraRing ICRS can be implanted more centrally than Intacs and, theoretically, for this reason they may have a greater effect than Intacs. Recently, Kubaloglu et al [9] confirmed this hypothesis. They compared the results of implantation of Keraring and Intacs ICRSs in keratoconic eyes and they found that Keraring ICRS led to more improvement in best corrected distance visual acuity (CDVA) and UDVA and a greater reduction in the maximum K value.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Intrastromal corneal ring segments (ICRS) are effective in flattening the corneal shape and improving vision for most recipients with keratoconus, but the magnitude of effect is highly variable; and inclusion of different implantation techniques, different types of ICRS, and patients with late stage disease in earlier studies [43][44][45][46] makes the existing evidence base for ICRS harder to interpret.…”
Section: Gross Corneal Shape Adjustment-intracorneal Ring Segmentsmentioning
confidence: 99%
“…[43][44][45][46][52][53][54][55][56] We would therefore argue for gross shape correction with ICRS implantation followed by CXL, fine shape correction with PRK if necessary, then finally pIOL implantation as a logical pathway to visual rehabilitation in grade II-III keratoconus (Figure 4). …”
Section: Refractive Correction-piol Implantationmentioning
confidence: 99%